Phase-Locking and Energy Enhancement of the Laser Accelerated Ions in the Radiation Pressure Regime - Disha Kumawat,; Krishna Kumar Soni, (International Journal of Scientific Research in Science and Technology, 2025)
Transversely inhomogeneous, intense laser pulse interacting with a mass-limited, ultra-thin dense target results in transverse plasma foil expansion. This expansion reduces the number of longitudinally accelerated ions phase-locked to the electromagnetic (EM) pulse, resulting in an increment in the forward-directed energy gain per ion. We present a study, combining theoretical and numerical analysis, on the energy transfer mechanism from an impinging laser to ions accelerated within a plasma foil. Furthermore, the phase relationship between the accelerated foil and the laser pulse are analyzed in this regime. Also, the transverse expansion is found to affect the relativistic transparency of the foil.
Keywords: Nonlinear Interaction; Ion Acceleration; Plasma Foil Expansion; Ion Energy Gain; Radiation Pressure Regime